Clay Types Modulate the Toxicity of Low Concentrated Copper Oxide Nanoparticles Toward Springtails in Artificial Test Soils. (13th September 2022) - Fischer, Jonas; Talal, Ghanem D. A.; Schnee, Laura S.; Otomo, Patricks V.; Filser, Juliane
Abstract: Copper oxide nanoparticles (CuO‐NPs) can be applied as an efficient alternative to conventional Cu in agriculture. Negative effects of CuO‐NPs on soil organisms were found, but only in clay‐rich loamy soils. It is hypothesized that clay–NP interactions are the origin of the observed toxic effects. In the present study, artificial Organisation for Economic Co‐operation and Development soils containing 30% of kaolin or montmorillonite as clay type were spiked with 1–32 mg Cu/kg of uncoated CuO‐NPs or CuCl2 . We performed 28‐day reproduction tests with springtails of the species Folsomia candida and recorded the survival, reproduction, dry weight, and Cu content of adults. In a second experiment, molting frequency and the Cu content of exuviae, as well as the biochemical endpoints metallothionein and catalase (CAT) in springtails, were investigated. In the reproduction assay, negative effects on all endpoints were observed, but only in soils containing montmorillonite and mostly for CuO‐NPs. For the biochemical endpoints and Cu content of exuviae, effects were clearly distinct between Cu forms in montmorillonite soil, but a significant reduction compared to the control was only found for CAT activity. Therefore, the reduced CAT activity in CuO‐NP‐montmorillonite soil might be responsible for the observed toxicity, potentially resulting from reactive oxygen species formation overloading the antioxidant system. This process seems to be highly concentration‐dependent, because all endpoints investigated in reproduction and biochemical assays of CuO‐NP‐montmorillonite treatments showed a nonlinear dose–response relationship and were constantly reduced by approximately 40% at a field‐realistic concentration of 3 mg/kg, but not at 32 mg/kg. The results underline that clay–CuO‐NP interactions are crucial for their toxic behavior, especially at low, field‐realistic concentrations, which should be considered for risk assessment of CuO‐NPs. Environ Toxicol Chem 2022;41:2454–2465. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.